In vitro antimicrobial activity of Muntingia calabura extracts and fractions - Zakaria, Zainul Amiruddin; Sufian, Adila Shahida; Ramasamy, Kalavathy; Ahmat, Norizan; Sulaiman, Mohd Roslan; Abdul Kadir, Arifah; Ahmad, Zuraini; Abdullah, Muhammad Nazrul Hakim (Academic Journals, 2010)
The aim of the present study is to determine the in vitro antimicrobial activity of various extracts, partitions and fractions of Muntingia calabura (Elaeocarpaceae) leaves against a selected panel of microorganisms. The leaves of M. calabura were soaked separately in the aqueous, chloroform and methanol solvent systems in the ratio of 1:20 (w/v) for 72 h and these procedures were repeated three times. Antimicrobial testing was carried out using the micro-broth dilution method. The microbes targeted were Staphylococcus aureus 25923, S. aureus 33591 (a multi-drugs resistant S. aureus (MRSA) isolate), Escherichia coli 35218, Pseudomonas aeruginosa ATCC 27853, Candida albicans 10231 and Microsporum canis ATCC 36299. The methanol extract inhibited MSSA (MIC = 1250 μg/ml; MBC = 1250 μg/ml) and MRSA (MIC = 1250 μg/ml; MBC = 1250 μg /ml) and considered the most effective extract and was further partitioned sequentially using the aqueous, petroleum ether and ethyl acetate. The ethyl acetate partition exhibited effective antibacterial activities with the MIC/MBC value of 156 and 313 μg/ml against S. aureus 25923 and S. aureus 33591, respectively. The ethyl acetate partition underwent fractionation process and yielded 15 fractions (A1-A15) of which only fractions A9 to A15 effectively inhibited the growth of S. aureus 25923 and S. aureus 33591 with MIC/MBC values ranging from 78 to 2500 μg/ml.